Electronic Nautical Charting: Economic Value and Role in Sustainable Development of Marine Transport Operations - Vadus, Joseph R. (The International Hydrographic Review, 2015)
Electronic nautical charting plays a major role in providing safe and efficient navigation of vessels primarily involved in commerce, fishery landings, marine recreation, cruises and research activities on the civil side, and naval operations for the military. In order to determine the contributions of electronic charting to marine transport operations, and the priorities for converting to electronic charts, this paper provides a general assessment of the economic value and importance of shipping operations in and out of U.S. ports including: foreign commerce, fishery landings, accidents, oil spills and military needs. This assessment will enable establishing priorities for electronic charts based on importance in serving U.S. Ports and U.S. Coast Guard Districts. Many accidents and spills are due to human error in ship navigation. In many cases these could be averted by using Electronic Nautical Charts (ENC) integrated with other navigation aids to provide features for collision/grounding avoidance. In its supporting role, ENC will help promote sustainable development of marine transport operations. In addition, ENC provides geodetically accurate coastal mapping data to serve as a reference base for Geographic Information Systems (GIS).